Photocatalysis: Oxidative Processes in Water Treatment - Roman V. Prihod'ko; Nely M. Soboleva (Journal of Chemistry)
The efficiency of various homogeneous and heterogeneous systems photocatalytic processes destructive oxidation of organic compounds of different classes is considered. It is shown that photocatalytic methods can significantly increase the speed and depth (up to complete mineralization) of decomposition processes of toxicants. The use of photocatalysis (PC) in the creation of low-power water treatment technologies is a promising direction in addressing environmental problems of the hydrosphere.